Ask a New Question
Search
Cole rewrote a quadratic function in vertex form. h(x)=x^2 -6x+7
Cole rewrote a quadratic function in vertex form. h(x)=x^2 -6x+7
Cole said that the vertex is (3, 2). Is Cole correct? If not,
1 answer
48 views
Cole rewrote the quadratic function h(x) = x^2 - 6x +7 into vertex form, Cole said the vertex is (3.2) is he correct? Show your
3 answers
45 views
Cole rewrote a quadratic function in vertex form.
h(x)= x^2−6x+7 Step 1: h(x)= (x^2−6x+ )+7 Step 2: h(x)=(x^2−6x+ 9 )+7
5 answers
38 views
Cole rewrote a quadratic function in vertex form.
h(x) = x²-6x+7 Step 1: h (x) = (x²-6x+)+7 Step 2: h (x) = (x²-6x+9)+7-9 Step
1 answer
62 views
Cole rewrote a quadratic function in vertex form.
h(x)= x^2−6x+7 Step 1: h(x)= (x^2−6x+ )+7 Step 2: h(x)=(x^2−6x+ 9 )+7
3 answers
42 views
Cole rewrote a quadratic function in vertex form.
h(x)= x2−6x+7 Step 1: h(x)= (x2−6x+ 9 )+7 Step 2: h(x)=(x2−6x+ 9 )+7 −9
1 answer
132 views
Cole rewrote a quadratic function in vertex form.
h(x)= x^2−6x+7 Step 1: h(x)= (x^2−6x+ )+7 Step 2: h(x)=(x^2−6x+ 9 )+7
1 answer
41 views
Cole rewrote a quadratic function in vertex form.
h(x)= x2−6x+7 Step 1: h(x)= (x2−6x+ )+7 Step 2: h(x)=(x2−6x+ 9 )+7 −9
1 answer
59 views
Cole rewrote a quadratic function in vertex form.
h(x)= x2−6x+7 Step 1: h(x)= (x2−6x+_) +7 Step 2: h(x)= (x2−6x+ 9)+7 −9
3 answers
51 views
Cole rewrote a quadratic function in vertex form. h(x)=x^2 -6 +7
1 answer
25 views